LABORATORIUM SEBAGAI SARANA PEMBELAJARAN KIMIA DALAM MENINGKATKAN PENGETAHUAN DAN KETRAMPILAN KERJA ILMIAH - Amna Emda (UIN AR-RANIRY, 2017)
Laboratory is one of the tool that is used to learn chemistry. In learning we expected that students not only know, but also understand the subject very well. Knowledge about theory that is scientific can be proved by doing some experiments in the laboratory. With the existence of the laboratory, students will understand more about the subject by doing scientific works. Therefore students will have a good grip on the scientific work’s step and their knowledge will last longer.